Expression of RNA-m6A-related genes correlates with the HIV latent reservoir level and the CD4+ and CD8+T cell profiles of patients with AIDS: Expression of RNA-m6A-related genes in patients with AIDS - Chen, Yahong; Lin, Shujin; Lai, Jinglan; Wang, Qiaowen; Lin, Jing; Ao, Wen; Ye, Hanhui; Han, Xiao (Cellular and Molecular Biology, 2023)
The HIV latent reservoir is the main obstacle to the eradication of AIDS. Recent studies have shown that the RNA m6A is involved in the regulation of HIV-1 replication. However, no relevant study has reported the relationship between RNA m6A and HIV latent reservoir. For this purpose, peripheral blood mononuclear cell (PBMC) was collected from 36 HIV-infected patients at 1, 24, and 48 weeks after treatment initiation. The number of CD4+ and CD8+ T cells was detected by flow cytometry. Amount of HIV DNA in the PBMC samples one week after treatment initiation was detected by Q-PCR. The expression levels of 23 RNA-m6A-related genes were detected by Q-PCR and Pearson’s correlation analysis was performed. Results showed that there was a negative correlation between HIV DNA concentration and the number of CD4+ T cells (r=-0.32, p=0.05; r=-0.32, p=0.06) and a positive correlation with the number of CD8+ T cells (r=0.48, p=0.003; r=0.37, p=0.03). Furthermore, a negative correlation was observed between HIV DNA concentration and the CD4+/CD8+ T cell ratio (r=-0.53, p=0.001; r=-0.51, p=0.001). RNAm6A related genes which correlated with HIV DNA concentration includedALKBH5 (r=-0.45, p=-0.006), METTL3 (r=0.73, p=2.76e-7), METTL16 (r=0.71, p=1.21e2.76e-06), YTHDF1 (r=0.47, p=0.004). Moreover, they have different degrees of correlation with numbers ofCD4+ and CD8+ T cell subsets, and the CD4+/CD8+T cell ratio. In addition, the expression of RBM15 was not correlated with HIV DNA concentration but was significantly negatively correlated with the number of CD4+T cells (r=-0.40, p=0.02). In conclusion, the expression of ALKBH5, METTL3, and METTL16 is correlated with the HIV DNA level, the levels of CD4+ and CD8+ T cell counts, and the CD4+/CD8+ T cell ratio. RBM15 is independent of HIV DNA level and negatively correlated with the number of CD4+T cells.